The Combined Effect of Birthing Ball Therapy and Birthing Yoga on Maternal Outcomes in Normal Delivery - Dwi Nur Octaviani Katili; Nour Arriza Dwi Melani; Alya Agustina Utiarahman (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Childbirth is a physiological process that can be accompanied by pain, anxiety, and varying duration of labor. When pain is not managed well, with high anxiety and too long labor duration, it can increase the risk of complications for the mother and baby, resulting in an increased risk of labor with medical procedures and labor trauma for the mother. One of the complementary therapies that can overcome these problems is the use of birthing balls and labor yoga. The purpose of this study was to analyze the effect of the combination of birthing balls and labor yoga on labor outcomes (labor pain, anxiety levels and labor duration). The research method used was Quashi Experiment with a Non-Equivalent Pretest-Posttest Control Group Design. The research subjects were mothers giving birth in the delivery room of RSIA Siti Khadijah, Gorontalo City with a purposive sampling technique based on inclusion and exclusion criteria, so that the total sample obtained was 50 mothers giving birth consisting of 25 respondents in the intervention group and 25 respondents in the control group. Data analysis used the T Test on the variables of Labor Pain and Anxiety Level and the Man-Whitney Test on the variable of labor duration. The results of this study indicate that the combination of birthing ball and birthing yoga has a distinct impact on labor outcomes. The greatest impact was seen on the psychological aspect, with a significant reduction in anxiety (p < 0.01), while the effects on labor pain and duration were more clinical-descriptive in nature without statistical significance (p > 0.05). Therefore, it can be concluded that the combination of birthing ball and birthing yoga predominantly affects the psychological aspect, while still contributing to expediting labor progress descriptively.